Tolerance fit based lubrication clearance design for sliding bearings in high power wind turbine gearboxes - LUO Yuan; LI Shengbo; ZHOU Yinchun; YUAN Xiangfei; HANG Yulei; SAVIN·Leonid; CHEN Zhaobo (Jixie chuandong)
ObjectiveRational design of sliding bearings widely employed in high-power wind turbine gearboxes is of critical importance. The bearing radial clearance directly governs lubrication regime, load distribution, friction loss, and vibration behavior. Optimizing clearance design not only ensures reliable operation but also enhances energy efficiency and prolongs service life under dynamic loading and harsh environmental conditions. Taking a sliding bearing in a high-power wind turbine gearbox as an example, a lubrication clearance design method is proposed that integrates tolerance fit specifications while accounting for surface roughness, geometric modifications, and thermal deformation effects.MethodsDesign calculations were independently conducted for the gear-bushing and bushing-shaft fits, and validation was performed through extreme-condition testing on an equivalent test rig under simulated operational loads and environmental constraints.ResultsThe results demonstrate that this method enables a reasonable configuration of the sliding bearing clearance, validating its correctness.